Academic Supervision and Teacher Performance: A Narrative Study at MA Al-Munawwarah Pondidaha - Toding, Muh. Rahmat; Syahrul, Syahrul; Mansyur, Mansyur (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This article aims to analyze several aspects, namely: 1) Stages of Academic Supervision Implementation by the Principal of Madrasah; 2) Supervision Approach by the Principal of Madrasah; and 3) Academic Supervision Techniques applied at MA Al-Munawwarah Pondidaha. The research was conducted qualitatively with a narrative approach, which is a form of investigation that presents data systematically, shows logical relationships and has meaning. The results of this study indicate that: 1) Stages of academic supervision are supervision planning, supervision implementation, and supervision evaluation; 2) The supervision approach used is a direct and indirect approach but the approach is closer to human supervision; 3) The supervision techniques used by the Principal of MA Al-Munawwarah Pondidaha are classroom visits, personal meetings (Individual conferences), teacher/staff council meetings, inter-class visits, meetings in work groups/MGMP, and seminars. Then the results of the supervision carried out by the principal of Madrasah MA Al-Munawwarah Pondidaha were able to improve teacher performance in terms of personality competency, professional competency, and social competency.